Mollecular Rapid Test Examination in Suspected Pulmonary Tuberculosis Patients at UPTD Puskesmas Siabu - Nisa El Hasanah; Benny Sihombing; Fitri Mulyani Siregar (Medistra Medical Journal (MMJ), 2026)
Tuberculosis (TB) is caused by Mycobacterium tuberculosis, causing damage to many body organs, such as the lungs, bones, brain membranes, stomach membranes, intestines, and even the urinary tract. This study aims to achieve early detection of pulmonary tuberculosis cases with rapid and accurate diagnosis at the UPTD Siabu Health Center. To obtain the number of suspected pulmonary tuberculosis patients examined using the Rapid Molecular Test at the UPTD Siabu Health Center Laboratory, from April to May 2025. This type of research is a descriptive analytical study. The results of the study showed that 16.1% (30 out of 187) of patients were confirmed positive for Rifampicin-Sensitive TB through the RMT. The distribution of positive cases was higher in males (16.7%) compared to females (15.2%). The age group ≥40 years had the highest number of TB cases (76.7% of total positives). Respondents with smoking habits showed a higher proportion of TB cases (63.3%) compared to non-smokers. Work as a farmer dominates positive cases (63.3%). In conclusion, these findings support the expansion of TCM implementation in primary healthcare facilities and emphasize the importance of gender-based and socio-environmental approaches in TB control strategies.